Presenting a Competitive Advantage-Based Technology Transfer Model Through a Grounded Theory Approach - Ahmadi, Pooneh; Heidari, Abbas; Shokrollahpour , Elsa (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: In today’s world, the aviation industry has become one of the most significant industries globally due to the ever-increasing global population and the rising demand for air travel. To enhance efficiency, reduce costs, and improve passenger experience, airline companies are seeking to transfer technologies based on competitive advantage and utilize big data to better their processes and decision-making. The current research aims to present a competitive advantage-based technology transfer model grounded in the grounded theory approach. Method: The research methodology employed is qualitative, based on the grounded theory strategy. Deep interview techniques were used for data collection. Through purposive sampling, theoretical saturation was achieved after 11 in-depth interviews. Findings: The grounded theory approach in this study entailed three coding stages: open, axial, and selective, identifying 22 general categories within a paradigm including causal conditions, context, intervening conditions, core categories, strategies, and outcomes. Conclusion: The results indicate that in today’s competitive business environment, airline companies are looking for ways to increase efficiency, improve passenger experience, reduce costs, and achieve a competitive advantage. To achieve such goals, the transfer of data-based technologies and competitive advantage is proposed as a significant strategy.